READING COMPREHENSION AND VOCABULARY MASTERY OF THE SIXTH GRADERS OF SDN 03 TENGGARONG - Samsu Armadi (Center of Language and Cultural Studies [CLCS], 2018)
This article describes the result of study on the relationship between reading comprehension to vocabulary mastery. Using correlational design, this study assigned 84 students of the sixth grade students of SDN 03 Tenggarong as the sample. The instruments of this study were test on reading comprehension and test on vocabulary mastery. Two kinds of data in terms of scores on reading comprehension and scores on vocabulary mastery were analyzed using product moment formula at p=0.05 and N=84. The study revealed that r-value was .802 and r-table was .294 (p=0.05). The hypothesis testing indicated that r-value was greater than r-table. The evidence showed that the study was significant, meaning that reading comprehension significantly relates to vocabulary mastery. The higher scores on reading comprehension allowed higher scores on vocabulary.